The long shadow of income on trustworthiness - John Ermisch; Diego Gambetta (Institute for the Study of Labor (IZA), 2011)
We employ a behavioural measure of trustworthiness obtained from an experiment carried out with a sample of the general British population whose individuals were extensively interviewed on earlier occasions. These previous interviews allow us to have very good income measures, and in particular to construct a measure of relative income that uses past income as a reference point. Our basic finding is that given past income, higher current income increases trustworthiness and, given current income, higher past income reduces trustworthiness. Past income determines the level of financial aspirations and whether or not these are fulfilled by the level of current income affects trustworthiness. But past income has a disproportionately large effect on trustworthiness compared to that predicted by the relative income theory, and this leads us to suspect that past income may also capture heterogeneity in relevant subjects' dispositions, with more opportunistic subjects being less trustworthy and having higher average incomes. We suggest and estimate a two-tier model in which relative income has the same positive effect within each past income class, but people in higher past income classes have a lower fundamental levels of trustworthiness.
urn:nbn:de:101:1-201104134071
Keywords: C93; D10; 330; trustworthiness; relative income; Vertrauen; Einkommen; Soziale Mobilität; Großbritannien